Modeling the Effects of Maternal Diabetes on the Developing Human Heart Using Pluripotent Stem Cell–Derived Heart Organoids. Issue 6 (20th June 2022) - Lewis‐Israeli, Yonatan R.; Abdelhamid, Mishref; Olomu, Isoken; Aguirre, Aitor
Abstract: Congenital heart defects (CHD) constitute the most common type of birth defect in humans. Maternal diabetes during the first trimester of pregnancy (pregestational diabetes, or PGD) is one of the most prominent factors contributing to CHD, and is present in a significant population of female patients with diabetes in reproductive age. PGD is challenging to manage clinically due to the extreme sensitivity of the developing embryo to glucose oscillations, and constitutes a critical health problem for the mother and the fetus. The prevalence of PGD‐induced CHD is increasing due to the ongoing diabetes epidemic. While studies using animal models and cells in culture have demonstrated that PGD alters critical cellular and developmental processes, the mechanisms remain obscure, and it is unclear to what extent these models recapitulate PGD‐induced CHD in humans. Clinical practice precludes direct studies in developing human embryos, further highlighting the need for physiologically relevant models. To bypass many of these technical and ethical limitations, we describe here a human pluripotent stem cell (hPSC)–based method to generate developmentally relevant self‐organizing human heart organoids. By using glucose and insulin to mimic the diabetic environment that the embryo faces in PGD, this system allows modeling critical features of PGD in a human system with relevant physiology, structure, and cell types. The protocol starts with the generation of hPSC‐derived embryoid bodies in a 96‐well plate, followed by a small molecule–based three‐step Wnt activation/inhibition/activation strategy. Organoids are then differentiated under healthy (normal insulin and glucose) and diabetic conditions (high insulin and glucose) over time, allowing for the study of the effects of pregestational diabetes on the developing human heart. We also provide an immunofluorescence protocol for comparing, characterizing, and analyzing the differences between the healthy and diabetic organoids, and comment on additional steps for preparing the organoids for analysis by other techniques after differentiation. © 2022 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Generation of hPSC‐derived embryoid bodies Basic Protocol 2 : Differentiation of EBs into heart organoids under healthy and diabetes‐like conditions Basic Protocol 3 : Immunofluorescence and organoid preparation for other assays